Arteriovenous malformation of the parotid gland: Diagnostic perspective- A case report - Hima John; S Padmashree; Padma Pandeshwar; Sayyad Zohabhasan Innus (Wolters Kluwer Medknow Publications, 2020)
Arteriovenous malformation (AVM) of the parotid gland is an extremely rare condition with very few cases reported in the literature. Majority of the swellings in the parotid region are usually due to sialadenitis, tumour etc., therefore making the initial diagnosis of vascular malformation may be difficult if there is no evident Turkey-wattle sign. Here, we present a case of AVM of parotid gland with its clinical features, radiographic features and its management. The lesion, being a high flow one, was managed with sclerosing agents to regress its size.